Hardware security and trust : design and deployment of integrated circuits in a threatened environment - Sklavos, Nicolas; Chaves, Ricardo; Di Natali, Giogio; Regazzoni, Francesco (Springer, 2017)
"This book provides a comprehensive introduction to hardware security, from specification to implementation. Applications discussed include embedded systems ranging from small RFID tags to satellites orbiting the earth. The authors describe a design and synthesis flow, which will transform a given circuit into a secure design incorporating counter-measures against fault attacks. In order to address the conflict between testability and security, the authors describe innovative design-for-testability (DFT) computer-aided design (CAD) tools that support security challenges, engineered for compliance with existing, commercial tools. Secure protocols are discussed, which protect access to necessary test infrastructures and enable the design of secure access controllers"--Provided by publisher.
Keywords: Computer security.; elektronické knihy; electronic books